KEPUASAN NASABAH DENGAN LAYANAN 24 JAM PADA PT. BANK MANDIRI (PERSERO) TBK. CABANG MAKASSAR - Dewi Pratiwi Indriasari (AkMen JURNAL ILMIAH, 2015)
The research goal is to determine and analyze the extent to which 24-hour banking service in PT. Bank Mandiri (Persero) Tbk. Makassar branch Panakukang affect the satisfaction of its customers, while the usefulness of the research is as inputs for PT. Bank Mandiri (Persero) Tbk. BRANCH Makassar Panakukang particular and for PT. Bank Mandiri (Persero) Tbk. Generally, about customer satisfaction banking services 24 hours of issuance. Results of the study can be used by observers of the banking issues, to assess the further development of information technology, especially the banking sector. Based on the analysis, it can be seen that Ho is rejected and Ha accepted. That proves that ATM Mandiri is very significant to give satisfaction to the customers of PT. Bank Mandiri (Persero) Tbk. BRANCH Panakukang Makassar. Based on the discussion above it can be concluded that the 24-hour banking services the bank has been very significant to give satisfaction to customers of PT. Bank Mandiri (Persero) Tbk. BRANCH Panakukang Makassar.